The occurrence of the toxins, streptol, kirkamide and pavettamine in the gousiekte-causing Rubiaceae species - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2024)
Dissertation (MSc (Medicinal Plant Science))--University of Pretoria, 2023.